PENGARUH KEGIATAN PKM TERHADAP KESIAPAN KERJA MAHASISWA DI LINGKUNGAN UNIVERSITAS PADJADJARAN - Agi Trigladi; Solehudin Solehudin; Nunung Nurhasanah (Universitas Bina Taruna Gorontalo, 2024)
This research aims to determine the influence of Student Creativity Program (PKM) activities on student work readiness at Padjadjaran University. Various programs have been created by the government to train students to develop skills in the world of work. One of the programs created to develop these skills is PKM activities. Padjadjaran University is one of the campuses that plays an active role in PKM activities. This activity was attended by various students to achieve a level of enlightenment in creativity and innovation based on mastery of science and technology. The research method used was by distributing questionnaires related to understanding the world of work. The data collection technique uses a survey method using a questionnaire given online via Google Form. The results of this research show that all students who have taken part in the PKM program have a good influence in facing the world of work. The conclusion that can be drawn from this research is that there is an influence of the PKM program which has been held at Padjadjaran University on readiness for the world of work.